Perlindungan Hukum Konsumen terhadap Investasi Emas Melalui Aplikasi Digital PT X: Tinjauan Terhadap Aspek Legalitas Perbuatan Hukum Campuran dan Perlindungan Konsumen - Oki Indra Setiono; Anwar Budiman; Retno Kus Setyowati (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study discusses the implementation of consumer law in the context of gold investment through PT X's digital application and the consumer protection guarantee mechanisms presented in the system. The research method used is normative juridical, namely a method that emphasizes the study of applicable positive legal norms, legal doctrine, and the application of relevant legal principles. The results of the study indicate that the implementation of consumer law in digital-based gold investment has been carried out in accordance with contractual principles as stipulated in civil law and in line with the provisions of Law Number 8 of 1999 concerning Consumer Protection. In practice, gold investment transactions through the X application are carried out with a mixed agreement containing elements of sale and purchase, deposit, and pawn. This is an important basis because the legal relationship between consumers and companies is not only a single transaction, but a combination that requires guaranteed protection of consumer rights. The legal basis for this mechanism is reflected in the X Digital Application Operational Guidelines Number 28 of 2024, which detailed administrative procedures, application usage requirements, and the implementation of consumer protection principles as stipulated in Articles 4, 7, 18, and 45 of the Consumer Protection Law. Thus, the implemented system not only emphasizes commercial aspects but also ensures a balance between the rights and obligations of consumers and businesses. This study highlights how digital transformation in financial services requires a robust legal framework to protect consumers from potential risks. Therefore, internal company regulations and guidelines play a strategic role in ensuring fairness and providing a sense of security for people investing in gold through digital applications.